2009
DOI: 10.1007/s10577-009-9035-0
|View full text |Cite
|
Sign up to set email alerts
|

Target chromosomes of inducible deletion by a Cre/inverted loxP system in mouse embryonic stem cells

Abstract: Chromosomal deletions are widely involved in serious genetic diseases and in the pathogenesis of cancers. These deletions often generate loss of heterozygosity (LOH) of one of the alleles of a tumor suppressor gene. Because of the technical difficulty inherent in genetic manipulation studies of a chromosome-wide deficiency, it has not been experimentally determined whether chromosome deletions could be a trigger for cancer development. Using the Cre/inverted loxP system, we have developed a chromosome eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In the second approach an active removal of the chromosome by exploiting cre-mediated rearrangements was proposed [ 19 ]. We tried to use this strategy, but the unexpected high frequency of the spontaneous loss of the endogenous engineered chromosome prevented us from implementing this approach, since normal substituted XY clones were easily obtained.…”
Section: Discussionmentioning
confidence: 99%
“…In the second approach an active removal of the chromosome by exploiting cre-mediated rearrangements was proposed [ 19 ]. We tried to use this strategy, but the unexpected high frequency of the spontaneous loss of the endogenous engineered chromosome prevented us from implementing this approach, since normal substituted XY clones were easily obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The recombination event appeared to be cytotoxic in the specific tissue analyzed (24). The same model has also been successfully utilized in chromosome deletion in embryonic stem cells (25)(26)(27). It was not known whether these detrimental effects apply to all adult tissue types and chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies using genetic engineering have revealed the possibility of performing aneuploidy therapy in cultured cells. Here, we summarize some of the main studies aimed at eliminating an entire chromosome using the Cre/loxP system [79][80][81][82][83][84][85], the TKneo transgene for positive and negative antibiotic selection [86], CRISPR/Cas9 system-mediated multiple cleavage [87,88], and zinc finger nuclease (ZFN)-mediated knock-in of the XIST gene to silence one copy of chromosome 21 [89] (cited in Table 2).…”
Section: Gene Targeting-mediated Chromosome Eliminationmentioning
confidence: 99%